The Sociology of popular proverbs in shaping Algerian culture - Boulakaibat, Naima (Journal of Human Sciences, 2020)
Literary discourse is a kind of social practice which expresses the consciousness of the group. Some of these speeches is practiced orally and is passed down through generations, resisting development, and affecting the culture of the society. This research focuses mainly on the relationship between the oral discourse and the building of cultural and social awareness, namely the folk proverbs and their relation with the building of Algerian cultural awareness.The purpose of this intervention is to study some folk proverbs to determine their impact on the cultural awareness of the society and to investigate the hidden patterns behind the production of these speeches.